Recursos humanos - Ortuño, Antonio, 1976- (Narrativas hispánicas, 2011)
Office worker Gabriel Lynch, determined to get the better of his fussy, privileged immediate boss, Constantino, meets a variety of people who are also motivated by ambition, envy, greed, and lust as he hatches his secret plot.